Impact of Nursing Interventions on Hospital Readmissions in Patients With Pulmonary Tuberculosis: A Quasi-Experimental Study - Chamlong Sunpapoa; Nat Na-Ek; Areeya Sommai; Kansak Boonpattharatthiti; Nina S. Huynh; Sukrit Kanchanasurakit (Asian Nursing Research, 2023)
Summary: Purpose: Our study aimed to evaluate the effectiveness of the nursing care program on the incidence and rate of 28-day hospital readmissions among pulmonary tuberculosis (TB) patients. Methods: We conducted a quasi-experimental study using a historical control (usual care) group. Patients diagnosed with pulmonary TB who received nursing interventions between January 28, 2021, and May 31, 2021, were categorized as an intervention group, whereas historical controls were selected from January 1, 2020, to December 31, 2020. The primary outcomes were the incidence and rates of hospital readmissions within 28 days due to TB-related complications. The secondary outcome was the change in knowledge and self-care behavior scores at discharge and 28 days postdischarge. Cox models were used to assess the intervention's impact on the incidence of hospital readmission. Rates of readmission were compared by the Poisson model. Both Cox and Poisson models were adjusted for age, sex, sputum smears at diagnosis, serum albumin level, and diabetes mellitus at baseline. Results: Among 104 pulmonary TB patients included in the analysis (68 were in a historical control group and 36 were in an intervention group), 20 patients were readmitted due to TB-related complications. We found that our nursing care program resulted in a significant reduction in the incidence (adjusted hazard ratio was 0.16 [95% CI 0.03, 0.87]) and the rate of hospital readmissions (adjusted incidence rate ratio was 0.22 [95% CI 0.06, 0.85]). Furthermore, nursing interventions significantly improved knowledge and self-care behavior scores with significant score retention at 28 days postdischarge. Conclusions: The nursing care program can significantly decrease the incidence and rate of 28-day hospital readmission and improve knowledge and self-care behavior scores in pulmonary TB patients.